Reduced gamma‐aminobutyric acid is associated with emotional and behavioral problems in Prader–Willi syndrome. Issue 8 (24th June 2016) - Rice, Lauren J.; Lagopoulos, Jim; Brammer, Michael; Einfeld, Stewart L.
Abstract : Prader–Willi syndrome (PWS) is characterized by infantile hypotonia, hypogonadism, small hands and feet, distinct facial features and usually intellectual impairment. The disorder is associated with severe behavioral disturbances which include hyperphagia leading to morbid obesity, temper outbursts, skin‐picking, and compulsive behaviors. While the brain mechanisms that underpin these disturbances are unknown these behaviors suggest a lack of inhibition and thus gamma‐aminobutyric acid (GABA), the main inhibitory neurotransmitter may be implicated. In the present study, we investigated in vivo brain GABA and its relationship with emotion and behavior in individuals with PWS. Single voxel proton magnetic resonance spectroscopy (1H‐MRS) was performed on 15 individuals with PWS and 15 age‐ and gender‐matched typically developing controls. GABA levels were measured in the parieto‐occipital lobe. All other metabolite levels (N‐acetyl aspartate, myo–Inositol, glutathione, glutamate, and glutamine + glutamate) were measured in the anterior cingulate cortex (ACC). GABA levels were significantly lower in the participants with PWS who had clinically significant emotional and behavioral problems relative to typically developing control participants and participants with PWS who did not have emotional and behavioral problems within the clinically significant range. GABA levels were negatively correlated with total behavioral problem scores as well as temper outbursts, skin‐picking, depression, social relating difficulties, and a tendency to be self‐absorbed. Our data suggests that alterations of the GABAergic system may play an important role in aspects of the pathophysiology of PWS. Pathological mechanism found in PWS may be relevant to understanding the control of similar behaviors in the general population. © 2016 Wiley Periodicals, Inc.